(untitled) (Journal of Economic Research & Business Administration, 2015)
The phrase “Kazakhstan car” is appeared since then when car assemble started in the country. Entrying into the Customs Union gives a stimulus to the development of auto industry in Kazakhstan. At the beginning of 2013 eleven existing assembly plants are registered in Kazakhstan. Totally 21,236 units of vehicles were collected by domestic car assembly plants in 2012. “AZIA AVTO” takes its leading position in car production volume and in the number of represented brands in Ust-Kamenogorsk, EKR. There is one more group of car companies «AllurAuto» and JSC «Kazakhstan Agromash Holding” in Kostanai. In the spring of 2014 the project “Industrial Engineering of Toyota» is starting in Kazakhstan. The production site for the assembly of the SUV Toyota Fortuner will be LLP “SaryarkaAvtoProm” in Kostanai. Thus the domestic car production has increased significantly recently and the operating companies do not intend to stop there.